A study on photovoltaic charging strategy of electric vehicles with multi-objective constraints. (18th August 2022) - Wu, Haowen; Wang, Chong; Zhou, Yudi; Xie, Wenwang; Chen, Chen
Installation of photovoltaic panels (PV) in a workplace for charging electric vehicles (EV) can help in both clean energy and ease of life. The disorderly charging behaviour of an EV photovoltaic charging station will aggravate the fluctuation of power grid distribution, and potentially affects the energy dispatching among electric vehicles, photovoltaic power generation and increasing cost. In order to solve these problems, we propose a photovoltaic charging strategy under multi-objective constraints. Taking the photovoltaic charging scene of electric vehicles, charging power and charging time of electric vehicles into account, the proposed solution can be formulated as a mixed integer linear programming task with multi-objective constraints. A wise charging strategy of electric vehicles is given by solving the formulated integer linear programming problem. Simulation results indicate that our proposed method is effective and useful to reducing charging cost.